If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v + v = 0 Combine like terms: v + v = 2v 2v = 0 Solving 2v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Divide each side by '2'. v = 0 Simplifying v = 0
| 4=2y+12 | | 74-v=47 | | w^2=3(w+-1) | | c+23=26 | | 5x-(7-x)=6x-7 | | -4+3x=-x+8 | | 9x(-3)= | | 13+6y=23 | | 2=26-4 | | t-21.7=47.1 | | 3+2y=3y-2 | | 6p+13=37 | | 2-7x+2x+1=3-5x | | 8r+28=76 | | 2.9n=13.34 | | -11+2x=-3+9 | | 1+2(y-5)=2y+2 | | 13+6w=43 | | x+7.3=12.8 | | 9*x*3=612x | | h+12.2=-12.2 | | x+7.3=12.1 | | (5x+4)(3x+8)= | | 4-6(2n-7)=25-5n | | x=-2.5+0.5y | | 3(x+5)-9=x+11 | | -x-3=-3x+5 | | 3+2m=3-4m+6 | | 0.798x=0.798 | | 24-h=4 | | h=-16x^2+100 | | 180-(20x+4)+8x+18+6x+4=180 |